Employers and Tourism Students Perception of Employability in Cruise Industry - Mary Ann Dumlao; Ian I. Llenares; Jay Sario (Philippine Association of Institutions for Research, Inc., 2018)
Despite challenges on the employability of tourism graduates, cruise industry emerged as potential labor market for aspiring tourism graduates in the field. This study aimed to understand the perception of employers and tourism students on employability and explore possible career opportunities. The mixed method research design was utilized such as survey and interview to gather data. The respondents were the 285 graduating tourism students in selected higher education institutions in Metro Manila and five recruitment officers of the three manning agencies, such as United Philippine Lines, Philippine Transmarine Carrier, and Magsaysay Shipping. The Phase I of the study focused on conducting the survey to know respondents perception on employment while Phase II concentrate on interview with the recruitment officers from the various manning agency to explore cruise tourism career opportunities. Results showed that tourism students perceived highly competent on cruise tourism jobs such as front office, food and beverages, housekeeping and cruise staffing expect for ship star reservation system and bar mixology. Also, they perceived high on graduate attributes such as customer expectation, innovative spirit, communication skills, organizational skills, self-management skills, self-awareness, self-reliant, leadership and assertiveness. Interestingly, employers perceived employability with outstanding skills on the front office, food and beverages, housekeeping and cruise staffing section.